Sistem Informasi Keselamatan dan Kesehatan Kerja Berbasis Web dengan Pemetaan Geografis untuk Deteksi Bahaya dan Pelaporan Insiden di Kampus - Adhwa Nabi; Ruminto Subekti; Cepi Ramdani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
K3L management in vocational campuses still runs manually. Incident reports are filled out on paper forms, hazard data is stored in separate spreadsheets across units, and there is no single view showing where hazards are located. This study develops a web-based K3L information system for Politeknik Manufaktur Bandung using Laravel 12, MySQL, and Leaflet.js as an interactive GIS map engine, following a Research and Development (R&D) method across eight stages. The system has seven main features: (1) interactive GIS mapping with hazard markers on OpenStreetMap; (2) GPS-based incident reporting via Web Geolocation API with campus polygon boundary validation and accuracy display in meters; (3) hazard reporting with mandatory GPS and building floorplan overlay; (4) voice-to-text using Web Speech API in Bahasa Indonesia across four text fields (chronology, cause, first aid action, and hazard notes); (5) automatic WhatsApp notifications to reporters and task force when reports are submitted or status is updated; (6) GPS location verification by task force on incident reports; and (7) a knowledge center and emergency center accessible without login. Testing used black box testing via Newman (79 requests, 237 assertions, 0 failures), UI smoke testing (22 scenarios, 0 failures), and User Acceptance Testing (14 scenarios from three actors, all accepted). The system transforms the previously fragmented manual K3L workflow into a single centralized digital platform monitored in real-time. This study contributes a practical model through a web-based occupational health and safety information system that integrates interactive GIS mapping, GPS, and voice-to-text in one centralized platform, serving as a replicable reference for K3L digitalization in vocational campuses that can be adapted by other educational institutions.